Promotion and evolution of sustainability performance measurement systems from a perspective of business process management: From a literature review to a pentagonal proposal - Pádua, Silvia Inês Dallavalle; Jabbour, Charbel José Chiappetta [UNESP] (Emerald, 2015)
Purpose – The purpose of this paper is to create a conceptual proposal that considers the relevant aspects to guide the promotion and evolution of corporate sustainability performance measurement systems (SPMSs) from a perspective of business process management. Design/methodology/approach – This study is divided into two phases. The first phase is a literature review with the study question was, “Which aspects need to be considered for promoting and evolving SPMS with a focus on business processes?” The second phase involved comparing these approaches and presenting a conceptual proposal with the relevant aspects for promoting and evolving a corporate SPMS. Findings – In the literature review, the following aspects were considered relevant to promoting sustainability: strategy, integration, stakeholders, evolution over time and business processes. The conceptual proposal found each aspect relevant and complementary presented consideration for each, forming one SPMS pentagon. Research limitations/implications – The comparison between the approaches is conceptual. Practical implications – This study can help organizations address the evolution of their measurement systems systemically. Originality/value – The summaries of the main considerations and evaluation issues provide starting points for organizations, researchers and students involved in sustainability-related matters. The discussion presented here can help organizations identify the strengths and weaknesses of their measurement systems and provide a basis for the promotion and implementation of improvements.
Keywords: Business process management; Corporate strategy; Measurement of performance; Pentagonal framework; Promotion of sustainability; Sustainability